Comparing the trophic structure of the Lvsi Fishing Ground as estimated from the Ecopath model and stable isotopic analysis. (5th November 2021) - Gao, Shike; Gong, Siming; Chen, Ze; Zhang, Xiao; Zhang, Shuo; Yu, Wenwen
Abstract: The trophic structure the Lvsi Fishing Ground (LSFG) ecosystem in the East China Sea was analyzed by using two methods: mass-balance modeling (Ecopath) and stable isotope analysis (SIA). Trophic levels (TLs) of the main functional groups estimated from the two methods were compared. The Ecopath model was built based on the fishery resource survey in the Lvsi Fishing Ground in 2018. Specifically, data on species composition, biomass, diet composition and fishey catches around the region were obtained from the survey. The model consisted of 14 functional groups, including plankton, benthos, fish, cephalopods, shrimps and crabs. TLs of the main functional groups were estimated to be between 2.00 (zooplankton) and 3.22 (congers). The total transfer efficiencies from levels II to VI were 2.84%, 20.41%, 19.27%, 19.31% and 19.32% respectively. Shrimps and trawling fisheries have major trophic impacts on most functional groups in the LSFG ecosystem. The total system throughput was estimated to be 7060 t km −2 year −1 . TLs derived from isotopic analysis were highly correlated with those estimated from Ecopath ( y = 0.6484 x +0.4715, R 2 = 0.83, P < 0.05). On average, Ecopath underestimated the TLs of the functional groups by approximately 8.83% compared to those estimated from SIA. This study suggests that these two complementary methods should be used together to validate trophic levels when balancing ecosystem structures. Highlights: In this study, we designed an Ecopath model to provide a quantitative description of the LSFG ecosystem for the first time, and compared the TLs of key functional groups estimated from SIA and Ecopath trophic dynamic modeling by using the LSFG ecosystem as a case study. Our purpose is to provide a theoretical reference for future next studies of ecological nutrition dynamics and basic parameters and scientific recommendations for the restoration of coastal ecological environments and rational utilization of ecological resources.